Fatigue crack growth behavior of wrought γ-based TiAl alloy containing β-phase. (September 2018) - Signori, Loris Jonathan; Nakamura, Taiki; Okada, Yotaro; Yamagata, Ryosuke; Nakashima, Hirotoyo; Takeyama, Masao
Abstract: The effect of microstructure containing β phase on the room temperature fatigue crack growth (FCG) behavior of a wrought TiAl alloy of Ti-43Al-4Nb-5V (at.%) was investigated. Three different microstructures which consist of α2 /γ colonies grains where the grain boundaries are decorated with an enrichment of volume fraction V DP of β/γ duplex microstructure were designed. The effects of β/γ duplex on stress intensity threshold and Paris slope have been determined. Fatigue crack growth curve were measured using the direct current potential drop technique. Crack pathway and fracture surface were examined by scanning electron microscope combined with in-situ CCD camera with the aim to evaluate the fracture mechanisms. It was found then even with a high-volume fraction of β phase V β, it is possible to maintain the FCG properties as same as for fully lamellar microstructure. Thus, the presence of β phase could improve the stress intensity threshold and decrease the Paris slope comparing to its corresponding β-free duplex microstructure. However, with increasing volume fraction of β/γ duplex, the FCG properties decrease and if the volume fraction of γ grains become too high, the fatigue crack growth behavior is mainly driven by the γ phase. Highlights: Importance of precrack introduction was demonstrated. Effect of β/γ phase on fatigue crack growth of wrought TiAl investigated. Important effect of β phase on fatigue stress intensity threshold. Effect of microstructure on local Paris slope have been investigated. Combined effect of β and γ enhanced the fatigue crack growth.